Violência conjugal: estudo sobre a permanência da mulher em relacionamentos abusivos - Marques, Tânia Mendonça (2005)
This work was developed in two phases. The first aimed to characterize women who suffer marital violence and their abusive partners and to determine the prevalence of different complaints, types of violence and criminal incidence. To fulfill the first stage, a survey was conducted in the archives of the Adida Women's Police Station to the Special Criminal Court and the Special Criminal Court of Uberlândia. A total of 876 records found in the Bulletins of Occurrence (BO) were examined in the first half of 2004 and 390 ongoing cases in the Circumstantial Terms of Occurrence (TCO) from January 2003 to May 2004. Analysis of the results showed that age The average number of women was 30.8 years and 32.31, respectively for BO and TCO, and among the most and the most frequently found women, victims of conjugal violence. Women live in different neighborhoods of Uberlândia and their occupations range from unemployed and from lai to businesswomen and professionals. The prevalence of complaints in TCOs was end of relationship, and in BOs were futile reasons, followed by absence of reasons. The threat to physical integrity was the most frequently reported crime, both in BO records and TCO records, respectively, description of violence and criminal incidence. The reports of marital violence occurred to couples whose relationship ranged from one month to 40 years of life in common. The highest incidence of BOs occurred at seven days, specifically revealing a high rate of weekend violence. A higher prevalence of threats was observed due to non-acceptance of the breakup, which shows that the fear of breaking a violent marital relationship is highly justified. In the second phase of the research, the causal attributions for the first and last episodes of violence were evaluated in a sample of 71 women who spontaneously sought the Uberlândia Women's Police Station to report a crime against their marital partner (TCO). The average age of women was 34.69 years, ranging in age from 17 to 59 years, mostly white, from different religions, professions and neighborhoods, and with children. The dating phase already revealed the problem of violence for 31% of women. Jealousy, nervousness, aggression, alcohol use, suspicion of being betrayed by her and his betrayal were the factors most often referred to as triggering aggressions. Physical and psychological aggression is a routine experienced by women. All the women interviewed lived with violent partners. To study the causes perceived by women for aggressions, a model proposed by Weiner was presented that predicts that a stimulus causes cognitions about its causes, causal cognitions or attributions determine affective responses and goal expectations, as well as subsequent behaviors. It was verified whether the focus of attribution, feelings and expectations were related to the woman's intention to stay or break up the marital relationship. The methodology used allowed the interviewees to classify the categories of attribution as recommended by Weiner, and also to categorize their feelings. Causal attributions were classified by women as internal to the first and last aggression and characterized as unstable and controllable for the first and stable and uncontrollable for the last. In addition, women exhibited a high frequency of partner blame for both episodes of violence. Women who attributed stable internal causes to partner violence, who expressed feelings against their partner, who had expectations that the situation would get worse if they remained in the relationship, demonstrated negative intentions in their partner, and a decent life expectancy if they left their partner reported intend to break up the relationship. The results suggest that women find it particularly difficult to break the relationship when they attribute unstable and controllable internal causes to their partners and are more likely to attribute uncontrollable stable internal causes to the violence committed by their spouse. These results support the psychosocial models that postulate that attributions are related to behavior and, particularly, to what was proposed in this study.